Charge-density wave associated with higher-order Fermi-surface nesting in monolayer VS2 - Tappei Kawakami; Katsuaki Sugawara; Hirofumi Oka; Kosuke Nakayama; Ken Yaegashi; Seigo Souma; Takashi Takahashi; Tomoteru Fukumura; Takafumi Sato (npj 2D Materials and Applications, 2023)
Abstract Fermi-surface (FS) nesting originating from Peierls’ idea of electronic instabilities in one-dimensional materials is a key concept to stabilize charge-density wave (CDW), whereas its applicability to two-dimensional (2D) materials is under intensive debate. Here we report unusual CDW associated with the higher-order FS nesting in monolayer 2D VS2. Angle-resolved photoemission spectroscopy and scanning tunneling microscopy uncovered stripe CDW with $$\sqrt {21} R10.9^° × \sqrt 3 R30^°$$ 21 R 10 . 9 ∘ × 3 R 3 0 ∘ periodicity together with an energy-gap opening on the entire FS. We suggest that this CDW involves the higher-order FS-nesting vector 2q twice larger than that of the normal one (q), as supported by the anomalies in the calculated phonon dispersion and electronic susceptibility. The present results suggest that the cooperation of q and 2q nesting leads to the fully gapped CDW state unlike the case of conventional single q nesting which produces a partial gap, pointing to an intriguing mechanism of CDW transition.